2018
DOI: 10.1016/s1470-2045(17)30891-4
|View full text |Cite
|
Sign up to set email alerts
|

Germline BRCA mutation and outcome in young-onset breast cancer (POSH): a prospective cohort study

Abstract: SummaryBackgroundRetrospective studies provide conflicting interpretations of the effect of inherited genetic factors on the prognosis of patients with breast cancer. The primary aim of this study was to determine the effect of a germline BRCA1 or BRCA2 mutation on breast cancer outcomes in patients with young-onset breast cancer.MethodsWe did a prospective cohort study of female patients recruited from 127 hospitals in the UK aged 40 years or younger at first diagnosis (by histological confirmation) of invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
256
6
27

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 342 publications
(336 citation statements)
references
References 30 publications
(49 reference statements)
23
256
6
27
Order By: Relevance
“…Regarding the breast cancer subtype, the prevalence of hormone receptor-positive cases was 44.7%, which is much lower than the results found in other developed countries in Asia, Europe and the US: 71% in Japan (Shibuta et al, 2011), 62% in Taiwan (Lin et al, 2009), 72% in Europe (Blows et al, 2010), and 72.7% in the US (Howlader et al, 2014). Our patients presented at young ages, with a mean age of 48 years old, and they tended to have higher histologic grade, and this trend can be observed in a recent study (Copson et al, 2018). The mean age is high in other developed countries in Asia, such as Japan (56 years) and Taiwan (50 years).…”
Section: Immunohistochemical Profilecontrasting
confidence: 54%
“…Regarding the breast cancer subtype, the prevalence of hormone receptor-positive cases was 44.7%, which is much lower than the results found in other developed countries in Asia, Europe and the US: 71% in Japan (Shibuta et al, 2011), 62% in Taiwan (Lin et al, 2009), 72% in Europe (Blows et al, 2010), and 72.7% in the US (Howlader et al, 2014). Our patients presented at young ages, with a mean age of 48 years old, and they tended to have higher histologic grade, and this trend can be observed in a recent study (Copson et al, 2018). The mean age is high in other developed countries in Asia, such as Japan (56 years) and Taiwan (50 years).…”
Section: Immunohistochemical Profilecontrasting
confidence: 54%
“…In a recently published cohort study of outcomes in early‐onset breast cancer, Copson et al () concluded that decisions regarding risk reducing strategies, such as CPM, should not only take into account ongoing cancer risk but also patient preferences (Copson et al, ). Our results show that a majority of women have strongly held preferences; they favour routine monitoring when choosing how they would manage the ongoing risk of cancer recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The POSH (Prospective Outcomes in Sporadic versus Hereditary breast cancer) study recruited young women (aged 18–40) diagnosed with primary breast cancer in the United Kingdom between 2000 and 2008 . The study methodology (including genotyping methods) and outcomes have previously been reported . Data on tumour focality/centricity in the POSH study patients was obtained from medical records from participating centres.…”
Section: Methodsmentioning
confidence: 99%